All-hazard emergency preparedness: an assessment of the hazard vulnerability and response capacity of secondary and tertiary hospitals in Riyadh Region, Saudi Arabia - Hajjam, Roaa (2024)
Introduction: Disasters pose a high risk of fatalities in many countries, and Saudi Arabia is not an exception. Extreme weather, mass gatherings, terrorism and fire can increase the intensity of disasters. When natural or man-made disasters happen, hospitals often bear the burden due to the need to admit many patients (victims of disaster events). The aim of the thesis is to assess the level of preparedness of secondary and tertiary hospitals in the Riyadh region for all types of hazards (all-hazard preparedness). Specifically, this study conducted an analysis of the vulnerability of hospitals to all types of hazards (all-hazard vulnerability). Functional emergency preparedness (preparedness for hazards that could prevent the hospital from performing its primary function), non-structural emergency preparedness (elements of hazard preparedness which require no physical infrastructure) emergency preparedness and capacity to respond to hazards for secondary and tertiary hospitals in Riyadh, Saudi Arabia were also assessed. Information on views of emergency managers were collected to understand challenges associated with the adoption and implementation of all-hazard approach to emergency preparedness in the region.